2001
DOI: 10.1034/j.1399-3038.2001.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide in asthmatic and non‐asthmatic children: Influence of type of allergen sensitization and exposure to tobacco smoke

Abstract: Asthmatic bronchial inflammation is associated with increased nitric oxide concentrations in exhaled air (eNO). Recent data suggest that this effect arises from atopy. Our aim in this study was to find out whether atopy and sensitization to particular allergens influences eNO levels. A total of 213 subjects (41 asthmatics and 172 controls) (96 boys and 117 girls, 7.3-14 years of age) were studied. Parents completed a questionnaire that sought information on their children's respiratory symptoms and exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
54
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 40 publications
12
54
1
Order By: Relevance
“…there was a substantial increase in eNO level in atopic asthmatics, whereas non-atopic asthmatics had a low eNO, similar to that of the control group. This result was also consistent with previous findings [16,21]. This difference between the two subgroups raises the question of whether the pathophysiological mechanisms of atopic asthma and non-atopic asthma are different.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…there was a substantial increase in eNO level in atopic asthmatics, whereas non-atopic asthmatics had a low eNO, similar to that of the control group. This result was also consistent with previous findings [16,21]. This difference between the two subgroups raises the question of whether the pathophysiological mechanisms of atopic asthma and non-atopic asthma are different.…”
Section: Discussionsupporting
confidence: 93%
“…As previously noted in adults [16] and in children [21], we found a low level of eNO that did not vary depending on the subjects' atopic or non-atopic status in the control group. This result was consistent with studies [22,23] that found no inflammatory modification of the bronchoalveolar lining in atopic or non-atopic healthy subjects.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, Leuppi et al 23 showed that in atopic children, an increased eNO level is associated with sensitization to perennial allergens but not with seasonal allergens. In addition, Barreto et al 19 reported no difference in eNO levels between nonatopic and atopic children sensitized to grass pollen. Thus, sensitization to indoor perennial allergens appears to affect eNO production in the respiratory tract, possibly through longlasting inflammatory stimuli, regardless of clinical respiratory manifestations.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, controversial results exist on the relation between sex and eNO levels; in fact, in some studies no association was found between sex and eNO. 18,19 In the study by Malmberg et al, 18 the authors demonstrated that height was a strong predictor of increased eNO in healthy children. The latter association was not found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The association of environmental tobacco smoke exposure and FeNO in children, however, is mixed, with no relationship in some studies and an inverse association in others. 21,22 Environmental exposures and asthma symptoms can vary by season, and these exposures affect asthma control. 23 One study, demonstrated that mean FeNO levels were higher in the winter than the spring, but only winter and spring FeNO levels were examined.…”
Section: Introductionmentioning
confidence: 99%